Effect of surface modification of colloidal silica nanoparticles on the rigid amorphous fraction and mechanical properties of amorphous polyurethane–urea–silica nanocomposites. Issue 24 (18th November 2019) - Oguz, Oguzhan; Candau, Nicolas; Bernhard, Stéphane H. F.; Kosak Soz, Cagla; Heinz, Ozge; Stochlet, Grégory; Plummer, Christopher J. G.; Yilgor, Emel; Yilgor, Iskender; Menceloglu, Yusuf Z.
ABSTRACT: Colloidal silica nanoparticles (NPs) modified with eight different silane coupling agents were incorporated into an amorphous poly(tetramethylene oxide)‐based polyurethane–urea copolymer matrix at a concentration of 10 wt % (4.4 vol %) in order to investigate the effect of their surface chemistry on the structure–property behavior of the resulting nanocomposites. The rigid amorphous fraction (RAF) of the nanocomposite matrix as determined by differential scanning calorimetry and dynamic mechanical analysis was confirmed to vary significantly with the surface chemistry of the NPs and to be strongly correlated with the bulk mechanical properties in simple tension. Hence, nanocomposites with an RAF of about 30 wt % showed a 120% increase in Young's modulus, a 25% increase in tensile strength, a 15% decrease in elongation at break with respect to the neat matrix, which had no detectable RAF, whereas nanocomposites with an RAF of less than 5% showed a 60% increase in Young's modulus, a 10% increase in tensile strength and a 5% decrease in the elongation at break. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2543–2556 Abstract : The influence of surface chemistry of colloidal silica nanoparticles modified with eight different silane coupling agents on the thermal and mechanical properties of amorphous polyurethane–urea–silica nanocomposites is reported. The fractions of mobile and rigid amorphous phases (MAF and RAF) are quantified. The filler surface chemistry is demonstrated to be of significance for the RAF, which provides a direct link between the nature and extent of the polymer–filler interactions and the mechanical properties of the resulting materials.